Conscious parents and their sense of coherence in education in the light Anthonovsky’s concept - Banach, Iwona (EDUsfera. Ewa Jurczyk-Romanowska, 2019)
The article contains reflections on modern parenting, awareness, and responsibilityin education. Educational awareness precedes the awareness of responsibility for creatinga family, its climate, and living conditions for all household members. Education carried out in a conscious manner, leading to the achievement of intended effects requires fulfillment of certain conditions. Educational impacts are subject to specific laws and rules. Respecting them largely determines the course of the educational process. Responsibility for upbringing is closely linked to parental responsibility, the basic feature of which is totality manifesting itself in all aspects of the child’s life. Parenthood is also a concern for the child’s proper social development and social skills. In the article, I referred to the conceptof A. Antonovsky’s sense of coherence, which can be successfully transferred to pedagogyand also applied to the process of education.
Keywords: parenthood; awareness; sense of coherence